Ukrainian Gastronomic Culture as a Social Phenomenon - Nikolenko, Vadim (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2016)
The article investigates the gastronomic culture as a social phenomenon. Emphasis is placed on the fact that gastronomy (culinary, gastronomic culture, dietary practices) is informative concept that provides the ability to highlight the specificity of the organization of the different dimensions of society. Ukrainian food culture has its own unique characteristics (variety of meatless dishes, unique gastronomic symbols of the nation, unique culinary standards gastronomic tradition), that distinguish it from other peers and are able to positively influence the formation of national identity.